Analisis Perilaku Peduli Lingkungan Siswa Kelas V di SDN Mugarsari - Mutaba'ah, Aini; Nugraha, Fajar; Wakih, Agus Ahmad (NUSRA : Jurnal Penelitian dan Ilmu Pendidikan, 2025)
This study aims to analyze the environmentally caring behavior of fifth-grade students at SDN Mugarsari and to identify the factors influencing such behaviors. Using a qualitative descriptive method, the research involved observations, interviews, and documentation with six students and one class teacher as participants. The results show that students demonstrate good environmental care, particularly in keeping the classroom clean and not littering. However, behaviors such as reducing plastic use and caring for school plants require improvement. Contributing factors include the role of the class teacher, school facilities, and students' environmental awareness. The study highlights the importance of early environmental education in shaping responsible behavior. During implementation, several obstacles remain, such as a lack of consistency between teachers and students, weak supervision, inadequate supporting facilities, and low student role models and awareness of environmental stewardship. To address these challenges, the school has implemented solutions such as teacher role models, regular education, visual reminders, improved sanitation facilities, and collaboration with parents. With consistent and collaborative efforts, the development of environmentally conscious character at SDN Mugarsari can be continuously strengthened and instilled in students.